Regional monetary policy: An Australian perspective - Fraser, Patricia; MacDonald, Garry; Mullineux, Andy (Routledge, 2012)
A structural vector autoregressive (SVAR) model for Australia is utilized to identify the domestic impacts of common monetary policy shocks on national and state business cycles and to consider the role of state diversification disparities for observed differences in responses to monetary policy innovations. Western Australia and Queensland differ to other states in their response to common shocks and evidence suggests this may be due to differences in their economic geographies. Overall, the Australian monetary union has become increasingly reliant on fiscal transfers particularly from Western Australia in the past two decades. This emphasizes the importance of a political union underpinning a successful monetary union.